Dysfunction of G Protein-Coupled Receptor Kinases in Alzheimer's Disease - William Z. Suo; Longxuan Li (The Scientific World Journal)
Although mutations and variations of several genes have been identified to be involved in Alzheimer's disease (AD), the efforts towards understanding the pathogenic mechanisms of the disease still have a long journey to go. One such effort is to identify the signal transduction deficits, for which previous studies have suggested that the central problems appear to be at the interface between G proteins and their coupled receptors. G protein-coupled receptor kinases (GRKs) are a small family of serine/threonine protein kinases primarily acting at the “receptor-G protein interface”. Recent studies have indicated the possible involvement of GRK, primarily GRK2 and GRK5, dysfunction in the pathogenesis of AD. It seems that mild, soluble, β-amyloid accumulation can lead to a reduced membrane (functional) and an elevated cytosolic GRK2/5. The increased cytosolic GRK2 appears to be colocalized with damaged mitochondria and neurofibrillary tangles. Moreover, the total levels of GRK2, not only in the brain, but also in peripheral blood samples, are increased in a manner inversely correlated with the patient's cognitive levels. The deficiency of GRK5, on the other hand, impairs presynaptic M2 autoreceptor desensitization, which leads to a reduced acetylcholine release, axonal/synaptic degenerative changes, and associated amnestic, mild cognitive impairment. It also promotes an evil cycle to further increase Beta-amyloid accumulation and exaggerates brain inflammation, possibly even the basal forebrain cholinergic degeneration. Therefore, continuous efforts in this direction are necessary before translating the knowledge to any therapeutic strategies.